2017
DOI: 10.1021/acs.est.6b06258
|View full text |Cite
|
Sign up to set email alerts
|

Public Health Risk of Arsenic Species in Chicken Tissues from Live Poultry Markets of Guangdong Province, China

Abstract: Arsenic-based feed additives, such as roxarsone (ROX), are still legally and widely used in food animal production in many countries. This study was conducted to systematically characterize the content and speciation of arsenic in chicken tissues from live poultry markets and in commercial chicken feeds in Guangdong, a major poultry production and consumption province in China, and to assess the corresponding public health risk. The total arsenic contents in the commercial feeds could be modeled as a mixture o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(35 citation statements)
references
References 43 publications
1
34
0
Order By: Relevance
“…The cumulative probability distribution of HQ is shown in Figure 7A, and the related statistical information is presented in Supplementary Table S6. The HQ values for Chinese adults for consuming MV ranged from 0.03 to 4.32, with 1.6% having a risk above the serious or priority level (HQ 1) (Hu et al, 2017), whereas that of MM, VP, SC, and CS ranged from 0.22 to 1.11, 0.02 to 1.82, 0.01 to 0.91, and 0.02 to 2.17, respectively, with only 0.002, 0.03, 0, and 0.08% having a health risk above the serious or priority level. Based on the USEPA's proposed cancer slope factor of 25.7 cases for an iAs dose of 1 mg kg-1 BW/d, the average daily consumption of MV may result in a mean of 16.5 cases of bladder and lung cancer per 100,000 Chinese adults with lifetime exposure (Supplementary Table S7).…”
Section: Health Risk Assessmentmentioning
confidence: 99%
“…The cumulative probability distribution of HQ is shown in Figure 7A, and the related statistical information is presented in Supplementary Table S6. The HQ values for Chinese adults for consuming MV ranged from 0.03 to 4.32, with 1.6% having a risk above the serious or priority level (HQ 1) (Hu et al, 2017), whereas that of MM, VP, SC, and CS ranged from 0.22 to 1.11, 0.02 to 1.82, 0.01 to 0.91, and 0.02 to 2.17, respectively, with only 0.002, 0.03, 0, and 0.08% having a health risk above the serious or priority level. Based on the USEPA's proposed cancer slope factor of 25.7 cases for an iAs dose of 1 mg kg-1 BW/d, the average daily consumption of MV may result in a mean of 16.5 cases of bladder and lung cancer per 100,000 Chinese adults with lifetime exposure (Supplementary Table S7).…”
Section: Health Risk Assessmentmentioning
confidence: 99%
“…Also according to their results, ROX concentrations decreased and i-As concentrations increased when the samples were cooked which showed that the cooking process had influence on arsenic forms [27,28]. Hu et al used HPLC-ICP-MS for speciation analysis of inorganic and organic arsenic species in chicken meat and both roxarsone and inorganic arsenic were detected at notably high amounts in chicken samples [29]. In an another study, cigarette filter was utilized as an adsorbent and coupled with HG-AFS for determination of total arsenic in various food samples such as vegetables, rice, chicken and fish [20].…”
Section: Introductionmentioning
confidence: 99%
“…p ‐Arsanilic acid ( p ‐ASA) and roxarsone (ROX) are common organic arsenic compounds widely used as feed additives to control the intestinal parasites in domestic animals. [ 4, 8, 9 ] However, p ‐ASA and ROX are often discharged into the environment along with animal faeces. [ 10, 11 ] Generally, p ‐ASA and ROX are deemed as low‐toxic compounds.…”
Section: Introductionmentioning
confidence: 99%